Formulation and Evaluation of Pharmaceutical Filament for 3D Printing Containing Lamotrigine - Joshi, Pallavi; Badola, Ashutosh (Journal of Neonatal Surgery, 2025)
This research explores the development and evaluation of a novel 3D printed oral drug delivery system for Lamotrigine using hot melt extrusion (HME) and fused deposition modeling (FDM) techniques. Polyvinyl alcohol (PVA) served as the polymeric carrier due to its biocompatibility and excellent printability, while triethyl citrate (TEC) was employed as a plasticizer to improve filament flexibility and processability. The Wellzoom hot melt extruder was utilized to manufacture drug-loaded filaments, which could be then printed into dosage forms using FDM. A comprehensive analysis, including thermal, mechanical, morphological, and other studies, was conducted to evaluate the performance and stability of the filament. The results demonstrated the potential for 3D printed Lamotrigine filament which highlighted the utility of this method for personalized medicine.